تأثير تصميم مقطورات نقل الحاويات على مقاومتها للتعب - نيرودا بركات; حاتم محمودي; أيهم دواي (Tishreen University, 2018)
The research aims to increase the fatigue resistance of container transport trailers used in ports and thus increase the life of these trailers by making modifications in the design of the trailers so that the value of the stresses resulting from the applied loads will decrease, thus increasing the number of load cycles that can be applied without collapsing the trailers. The value of the stresses formed as minor design changes lead to significant changes in the value of the stresses. يهدف البحث إلى زيادة مقاومة مقطورات نقل الحاويات للانهيار تحت تأثير التعب التي تستخدم في المرافئ وبالتالي زيادة عمر هذه المقطورات وذلك من خلال إجراء تعديلات في تصميم المقطورات بحيث تقل قيمة الإجهادات الناتجة عن الحمولات المطبقة وبالتالي سيزداد عدد دورات التحميل الممكن تطبيقها دون أن تنهار المقطورات ويبين البحث تأثير التصميم على قيمة الإجهادات المتشكلة حيث أن تغيرات بسيطة في التصميم تؤدي إلى تغيرات كبيرة في قيمة الإجهادات.